ANALISIS PENGELOLAAN RISIKO OPERASIONAL SUATU BISNIS JASA EKSPEDISI LAUT UNTUK MEMUASKAN STAKEHOLDERS (Kasus pada PT. NAGAH BERLIAN cabang BELAWAN, SUMATERA - Hutasuhut, Hari Fahmy; Zuliarni, Sri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The operational risk management is a very important thing to do by all companies,both companies of goods or services. This is done in order to the company can reduce or even to eliminate, the risk operational in the activity up to cause not the dekriments for the company.The purpose of the research is to identfy and to know the risk operational profile also to analyse expedition business risk management on PT. Nagah Berlian cabang Belawan, North Sumatera to satisfy the stakeholders.The method on research is how te process of the operational risk management that done by PT. Nagah Berlian, the sorce of the data used are primary data,the data is in the form of interviews through FGD mini or mini-group discussions with informants who the considered in answering the questions and which is directly connected with activity of operational risk management and secondary data, the data like datas that optained and summitted from PT. Nagah Berlian cabang Belawan, North Sumatera, Jl. Pelabuhan II No 1A, Belawan contains information relating to this research, such company profile, organitation structure, the list of ship fleet and the other data which is relevant with this research.The result of the research that doing was show that there are four ways in operational risk management done by PT. Nagah Berlian cabang Belawan, North Sumatera, including: to smallen the risks, to shift the risks, to control the risks, and the risk fundation.Keywords: risk management, stakeholders, marine services business expedition